2017
DOI: 10.1002/2017jd026567
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of marine aerosol subgrid variability and its correlation with clouds based on high‐resolution regional modeling

Abstract: One limitation of most global climate models (GCMs) is that with the horizontal resolutions they typically employ, they cannot resolve the subgrid variability (SGV) of clouds and aerosols, adding extra uncertainties to the aerosol radiative forcing estimation. To inform the development of an aerosol subgrid variability parameterization, here we analyze the aerosol SGV over the southern Pacific Ocean simulated by the high‐resolution Weather Research and Forecasting model coupled to Chemistry. We find that withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…These discrepancies do not stop at physical observations. Current global climate models operate over spatial grids that can span hundreds of kilometres per grid box and sub-grid variability within these boxes can significantly limit the accuracy of the model, particularly for aerosol parameters such as CCN (Lin et al, 2017;Weigum et al, 2016). Given the highly dynamic conditions within the Southern Ocean and the limited and sometimes conflicting observations reported to date, further investigation is required to identify the main factors contributing to aerosol variability.…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies do not stop at physical observations. Current global climate models operate over spatial grids that can span hundreds of kilometres per grid box and sub-grid variability within these boxes can significantly limit the accuracy of the model, particularly for aerosol parameters such as CCN (Lin et al, 2017;Weigum et al, 2016). Given the highly dynamic conditions within the Southern Ocean and the limited and sometimes conflicting observations reported to date, further investigation is required to identify the main factors contributing to aerosol variability.…”
Section: Introductionmentioning
confidence: 99%
“…The global and annual averages of the ratio for the AOT are calculated to be 28.5% (HRM) and 16.6% (LRM). The value obtained from only the HRM ranges between the two values obtained by Lin et al (2017). For the CCN at a height of 2 km, the values are relatively small (7.6% for the HRM and 4.1% for the LRM),…”
mentioning
confidence: 48%
“…In addition to the impact of the model grid size on the monthly averages of the aerosol concentrations at the relevant sites, the temporal variations in the aerosol concentrations are also investigated. Such comparisons were carried out by Lin et al (2017), who investigated the marine aerosol subgrid variability using a regional HRM over the southern Pacific Ocean. Lin et al (2017) estimated variabilities in the aerosol mass concentrations of 15% near the surface and 50% in the free troposphere in a 180-km×180-km domain using 3-hourly 3-km×3-km original grids for October 2008.…”
mentioning
confidence: 99%
“…Aerosol subgrid cloud‐scale vertical transport and wet removal are closely related to clouds and usually take place on scales smaller than the traditional global climate model (GCM) grid size (typically about 100 km). Previous studies have shown the existence of large variability for aerosol processes on scales smaller the GCM grid box (Lin et al, ; Qian et al, ). This poses a significant challenge to representing aerosol lifecycles in traditional GCMs.…”
Section: Introductionmentioning
confidence: 99%
“…We found that (1) the MMF with aerosol processes explicitly represented in CRM grid cells can improve aerosol simulations in many aspects.(2) the MMF with aerosols parameterized in GCM grid cells can cause great biases in modelled aerosol distributions.Aerosol subgrid cloud-scale vertical transport and wet removal are closely related to clouds and usually take place on scales smaller than the traditional global climate model (GCM) grid size (typically about 100 km). Previous studies have shown the existence of large variability for aerosol processes on scales smaller the GCM grid box (Lin et al, 2017;Qian et al, 2010). This poses a significant challenge to representing aerosol lifecycles in traditional GCMs.…”
mentioning
confidence: 99%